Electronic Education Payment System Using Design Thinking Method At Mis Muhajirin - Sahfitri, Lala Pricilia; Nasution, Muhammad Irwan Padli (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2024)
Electronic Education Payment information system is an education fee payment system using online payment technology. However, the tuition payment system at MIS Muhajirin is still done manually by recording each payment transaction using the SPP card. This is an obstacle because it causes long queues by parents when paying tuition fees and there is also a high possibility of human error. This research aims to produce a web-based online payment information system at MIS Muhajirin, as well as to determine the level of efficiency if implemented at MIS Muhajirin. The method used in this research is the Design Thinking method which consists of 5 stages, namely Empathize, Define, Ideate, Prototype, and Test. The results of the research show that the information system developed provides effectiveness for admin staff when managing tuition payments at MIS Muhajirin and provides convenience for parents in terms of paying tuition online and not having to queue at school as before. Thus it can be concluded that this application is quite influential in improving the effectiveness and efficiency of the tuition payment system at MIS Muhajirin